2009
DOI: 10.1002/clc.20611
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal Prohormone Brain Natriuretic Peptide‐proBNP Levels in Ventricular Arrhythmias in Children

Abstract: Background Ventricular arrhythmias are the most common consequences of structural and functional heart diseases, but cases with no evident pathology are also observed. A parameter indicating asymptomatic circulatory failure could support decisions related to possible treatment of ventricular arrhythmias. Hypothesis The study objective was the evaluation of N‐terminal prohormone brain natriuretic peptide (NT‐proBNP) levels in children with ventricular arrhythmias and an attempt to determine if this parameter ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Lindholm et al [ 34 ] confirmed that NT-proBNP and hs-cTnT had greater prognostic value than any other biomarkers for cardiovascular outcomes. In a study of ventricular arrhythmias in children, Mazurek et al [ 35 ] found that the level of NT-proBNP increased with the severity of the ventricular arrhythmia, and the determination of NT-proBNP is helpful for the diagnosis and grading of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Lindholm et al [ 34 ] confirmed that NT-proBNP and hs-cTnT had greater prognostic value than any other biomarkers for cardiovascular outcomes. In a study of ventricular arrhythmias in children, Mazurek et al [ 35 ] found that the level of NT-proBNP increased with the severity of the ventricular arrhythmia, and the determination of NT-proBNP is helpful for the diagnosis and grading of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Patients younger than 18 years with CHD who underwent cardiac surgery were eligible for the study. Children who had preoperative arrhythmia (potentially malignant ventricular arrhythmias and high-degree atrioventricular block), rheumatic heart disease, infective endocarditis, myocarditis, pericardial disease, renal dysfunction, or neoplasms, [10][11][12] or who could not be separated from cardiopulmonary bypass (CPB) were excluded.…”
Section: Patients and Methods Subjectsmentioning
confidence: 99%
“…It showed PVCs originating from tricuspid valve were associated with highest burden and highest NT-proBNP and reduced ejection fraction (even less than 50% in some patients). A study conducted by Mazurik B et al 10 established the association of PVCs with NT-proBNP in children. Present study was conducted on adults while children were excluded, but its result coincides with that study and both studies found signi cantly raised NT-proBNP levels in moderate and frequent PVCs burden in comparison to control group.…”
Section: Discussionmentioning
confidence: 99%